Soil temperature explains radial growth of coniferous trees more effectively than air temperature in mountainous cold temperate habitat - Minghao Cui; Yuan Jiang; Feng Xue; Penghe Cao; Muyi Kang (Ecological Indicators)
The radial growth status of trees is an important indicator for measuring forest productivity. With the aim to distinguish the responses to air and soil temperature in their radial growth, we monitored the stem radius variations of larch (Larix principis-rupprechtii) and spruce (Picea meyeri) in sub-alpine habitat in North-central China using point dendrometers over a five-year period from 2018 to 2022, analyzed the intra-annual radial growth characteristics of these two species and their relationship with the environment. The results showed that the onset of radial growth, the day with maximum rate, and the cessation of radial growth of larch were 7, 6, and 4 days later than that of spruce, respectively; the maximum rate and annual increment of larch were significantly higher than that of spruce. The soil temperature contributed more to the annual increment and the maximum rate of radial growth than the air temperature did. Meanwhile, the soil temperature demonstrated a threshold value for initiating the radial growth of trees, and the value for larch’s was at a daily average soil temperature of 3.0 °C and for spruce’s was at 2.0 °C. In addition, the maximum radial growth rate in larch was indirectly influenced by air temperature through the vapor pressure deficit (VPD), whereas that in spruce was affected by soil water content. We concluded that soil temperature explained radial growth of conifers more effectively than air temperature. Our findings suggested that incorporating soil factors into models simulating and predicting forest productivity could greatly enhance the accuracy of modeling.